Asymptomatic Clostridium difficile colonization: epidemiology and clinical implications. Issue 1 (December 2015) - Furuya-Kanamori, Luis; Marquess, John; Yakob, Laith; Riley, Thomas; Paterson, David; Foster, Niki; Huber, Charlotte; Clements, Archie
Abstract Background The epidemiology ofClostridium difficile infection (CDI) has changed over the past decades with the emergence of highly virulent strains. The role of asymptomaticC. difficile colonization as part of the clinical spectrum of CDI is complex because many risk factors are common to both disease and asymptomatic states. In this article, we review the role of asymptomaticC. difficile colonization in the progression to symptomatic CDI, describe the epidemiology of asymptomaticC. difficile colonization, assess the effectiveness of screening and intensive infection control practices for patients at risk of asymptomaticC. difficile colonization, and discuss the implications for clinical practice. Methods A narrative review was performed in PubMed for articles published from January 1980 to February 2015 using search terms 'Clostridium difficile' and 'colonization' or 'colonisation' or 'carriage'. Results There is no clear definition for asymptomatic CDI and the terms carriage and colonization are often used interchangeably. The prevalence of asymptomaticC. difficile colonization varies depending on a number of host, pathogen, and environmental factors; current estimates of asymptomatic colonization may be underestimated as stool culture is not practical in a clinical setting. Conclusions AsymptomaticC. difficile colonization presents challenging concepts in the overall picture of this disease and its management. Individuals who are colonized by the organism may acquire protection from progression to disease, however they also have the potential to contribute to transmission in healthcare settings.